Euryglossina (Euryglossina) perpusilla (Hymenoptera: Colletidae: Euryglossinae) nesting in pre-formed cavities in Banksia attenuata (Proteaceae) - Prendergast, Kit Stasia (Journal of Melittology, 2018)
This article reports observations of nesting by Euryglossina (Euryglossina) perpusilla Cockerell, 1910 in preformed cavities in a Banksia attenuata tree in an urban bushland remnants.